O06 Hepatitis c transmission in hiv negative men who have sex with men (msm) who do not inject drugs. (8th June 2017) - Fitzpatrick, Colin; Pinto-Sander, Nicolas; Williams, Deborah; Richardson, Daniel
Abstract : Introduction: Since 2000 there has been an increase in reported acute hepatitis C in HIV infected men who have sex with men which is associated with injecting drug use (IDU), condomless anal sex, pre-exposure prophylaxis (PrEP) use and sexual practices including fisting. There have been very few reports of acute Hepatitis C in HIV negative MSM who do not inject drugs. Locally we have been screening all MSM and IDUs per year for Hepatitis C since 2005. Methods: We looked at cases of hepatitis C diagnosed in our sexual health/HIV service per calendar year from 2012 – 2016 and looked at HIV status, injecting drug use and sexual behaviour. Results: We saw 37, 012 attendances for sexually transmitted infection testing by MSM in the study period: There were 9 diagnoses of hepatitis C in HIV negative MSM in the study period. (2012:3, 2013:3, 2014:1, 2015:2, 2016:0). 5/9 HIV negative MSM diagnosed with hepatitis C gave a history of IDU. 4/9 HIV negative MSM diagnosed with (incident) Hepatitis C had no documented history of IDU, all had a recent history of condom-less anal sex at chem-sex parties; 2/4 had engaged in fisting and none were using PrEP at the time of diagnosis. Discussion: There appears to be a very small amount of hepatitis C transmission in HIV negative MSM who do not inject drugs associated with condom-less anal sex at chem-sex parties and fisting. Screening for hepatitis C could be rationalised to these groups of MSM.